An explanation of lean six sigma barriers Malaysia wastewater treatment chapter - Ishak, Anuar; Mohamad, Effendi; Arep @ Ariff, Hambali; Ito, T. (2023)
This study examines Lean Six Sigma (LSS) implementation challenges in Malaysian wastewater treatment plants (WWTPs) to enhance the sustainability. LSS, known for waste reduction through the “reduce, reuse, and recycle” (3R) principles and statistical process stability, has excelled in manufacturing but faces hurdles in WWTPs. The need arises to consolidate LSS knowledge and identify key barriers. Findings indicate that “Management Barriers” (MgtBars) significantly influence “Resource Barriers” (ResBars), “Knowledge Barriers” (KnwBars), and “Process Barriers” (PrcBars) with a p-value < 0.005. This emphasizes the urgency for skilled WWTP personnel to adopt LSS, thereby improving compliance and wastewater treatment service quality.